(untitled) (Eurasian Journal of Engineering and Technology, 2025)
This article analyzes the key factors influencing the environmental situation in the Republic of Uzbekistan, including global climate change, the issue of transboundary resources, anthropogenic pressure, and institutional features of environmental governance. It highlights the political, social, and economic consequences of major ecological threats such as the Aral Sea disaster, water scarcity, soil degradation, air pollution, and waste management challenges. The study emphasizes the importance of a political approach to environmental issues, the need for improved environmental governance, and the significance of aligning national policies with international environmental commitments